Magnesium Homeostasis in Cardiac Myocytes of Mg-Deficient Rats - Tashiro, Michiko (Public Library of Science, 2013)
To study possible modulation of Mg(2+) transport in low Mg(2+) conditions, we fed either a Mg-deficient diet or a Mg-containing diet (control) to Wistar rats for 1–6 weeks. Total Mg concentrations in serum and cardiac ventricular tissues were measured by atomic absorption spectroscopy. Intracellular free Mg(2+) concentration ([Mg(2+)](i)) of ventricular myocytes was measured with the fluorescent indicator furaptra. Mg(2+) transport rates, rates of Mg(2+) influx and Mg(2+) efflux, were estimated from the rates of change in [Mg(2+)](i) during Mg loading/depletion and recovery procedures. In Mg-deficient rats, the serum total Mg concentration (0.29±0.026 mM) was significantly lower than in control rats (0.86±0.072 mM) after 4–6 weeks of Mg deficiency. However, neither total Mg concentration in ventricular tissues nor [Mg(2+)](i) of ventricular myocytes was significantly different between Mg-deficient rats and control rats. The rates of Mg(2+) influx and efflux were not significantly different in both groups. In addition, quantitative RT-PCR revealed that Mg deficiency did not substantially change mRNA expression levels of known Mg(2+) channels/transporters (TRPM6, TRPM7, MagT1, SLC41A1 and ACDP2) in heart and kidney tissues. These results suggest that [Mg(2+)](i) as well as the total Mg content of cardiac myocytes, was well maintained even under chronic hypomagnesemia without persistent modulation in function and expression of major Mg(2+) channels/transporters in the heart.